Analisis Kebijakan Penataan Lingkungan di Kota Sungai Penuh - Kuswandi, Rudi; Frinaldi, Aldri; Saputra, Kiki (Jurusan Ilmu Sosial Politik, Fakultas Ilmu Sosial, Universitas Negeri Padang, 2023)
This study aims to examine the application of environmental policy in Sungai Penuh City, Jambi Province, utilizing perspectives from state administration law. The primary focus is to identify challenges encountered during implementation. Employing a qualitative approach, this research draws data from literature reviews, observations, interviews, and documentation. Data analysis involves manual reduction, presentation, and interpretation. The study reveals the existence of various environmental policies, notably the Sungai Penuh City Regional Spatial Plan (No. 5 of 2012) for 2011-2031 and the Environmental Protection and Management Plan (No. 4 of 2022) for 2022-2052. However, the efficacy of these policies within the environmental department of Sungai Penuh City remains suboptimal due to improper waste disposal practices among numerous small businesses. Furthermore, several challenges impede the execution of environmental management policies in the city, including limited government funding, inadequate staffing, insufficient coordination among relevant agencies, and a lack of awareness and commitment to environmental sustainability among business entities.